The Effect of Turmeric Decoctum to the Angiogenic Molecules Expression on Chicken Embryo - Zahariah, Sultanah; Winarsih, Sri; Baktiyani, Siti Candra Windu; Rahardjo, Bambang; Kalsum, Umi (Journal of Tropical Life Science, 2017)
Turmeric (Curcuma longa) is widely used as herbal medicine, not an exception by pregnant women. Turmeric consumption by expectant mothers requires standard dose, because of its antiangiogenic effect could be harmful on placentation process and embryonic development. This experiment was undertaken to determine the effect of different concentrations of turmeric decoctum to the expression of Vascular Endothelial Growth Factor Receptor-2 (VEGFR-2) and Angiopoietin 1 (Ang-1) on the 48-hours-old chicken embryo. In this study, turmeric was extracted using decoction method to mimic the common method as adopted by people. The turmeric decoctum were freeze dried into a powder form and was used in preparing the stock solution for 200 ppm (P1), 300 ppm (P2), and 400 ppm (P3) as experimental treatments. The control group (P0) received 2% DMSO without turmeric decoctum. These were administered on the yolk sack of 16 hours incubation of fertile chicken egg by number of 200 ÂµL. After 48 hours incubation, the expression of VEGFR-2 and Ang-1 on the chicken embryo were counted by ImageJ software. The results revealed that there is no significant effect of turmeric decoctum to the expression of VEGFR-2 and Ang-1. This suggested that turmeric decoctum was safe up to 400 ppm on chicken embryo.